2018
DOI: 10.21547/jss.316178
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Cultural Heritage by Means of Museums in an Ever-Changing World

Abstract: The main objective of this comparative study is to understand and analyse the sustainability perspectives of museums in France, Canada, Sweden, Turkey and Greece. By adopting a qualitative research approach, data were gathered from eleven museum officials in five different countries. As an interesting result of the study, an advanced use of technology was seen at the oldest museum of the research sample. Overall, the comparative analysis revealed that general sustainability efforts, use of technology in presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…It presents and reinforces the importance of the fine arts and visual culture in the value system of the global community, increasing self-generated revenue (Tate Modern). The findings of previous authors Ferika and Nazli 2018) are confirmed by the mission statements, which emphasize that although achieving economic stability is a challenge, it is an important prerequisite for addressing other dimensions of sustainability.…”
Section: Economic Stabilitysupporting
confidence: 54%
See 1 more Smart Citation
“…It presents and reinforces the importance of the fine arts and visual culture in the value system of the global community, increasing self-generated revenue (Tate Modern). The findings of previous authors Ferika and Nazli 2018) are confirmed by the mission statements, which emphasize that although achieving economic stability is a challenge, it is an important prerequisite for addressing other dimensions of sustainability.…”
Section: Economic Stabilitysupporting
confidence: 54%
“…The economic sustainability of museums is mostly understood in the literature in terms of funding, but it is important to complement this with the role of the market and the impact of innovation and technology (Fehér et al 2021). However, achieving economic stability is a challenge for museums, and in many cases, therefore museum managers do not address the issue of sustainability (Ferika & Nazli 2018). However, we also see approaches where museums take advantage of the competitive advantage of the term 'being green' .…”
Section: Sustainability In Museumsmentioning
confidence: 99%
“…The programme also supports artists to participate at international exhibitions. Art collection and preservation: the NGZ has a museum that manages a collection of pre-colonial to contemporary art of all forms including sculpture. Its role is to exhibit legitimate artworks and preserve cultural achievements of the past (Özer Sarı and Nazlı, 2018: 3, 6–9). Thus, observes Joy and Sherry (2003:162) that the inclusion of an artist's works in a collection of a museum is an endorsement of the quality of the artworks. Arts education: Through the Education Department, NGZ conducts workshops and lectures on different visual art subjects; Conducts guided tours through an outreach programme; Runs annual schools’ art exhibitions, and; Hosts the National Gallery School of Visual Arts and Design (NGSVAD) that offers training in different fields of art practice at diploma level. Indigenous communities of practice: these are the springboard of collective art activities of informal visual artists.…”
Section: Presentation and Discussion Of Findingsmentioning
confidence: 99%
“…Art collection and preservation: the NGZ has a museum that manages a collection of pre-colonial to contemporary art of all forms including sculpture. Its role is to exhibit legitimate artworks and preserve cultural achievements of the past (Özer Sarı and Nazlı, 2018: 3, 6–9). Thus, observes Joy and Sherry (2003:162) that the inclusion of an artist's works in a collection of a museum is an endorsement of the quality of the artworks.…”
Section: Presentation and Discussion Of Findingsmentioning
confidence: 99%